Pengungkapan Intellectual Capital : Mandatory atau Voluntary? - Noorina Hartati (Jurnal Akuntansi dan Bisnis, 2014)
Intellectual Capital began ogled by the stakeholders because of its existence as an intangible asset that is no less important to tangible assets.. Therefore, these companies began to actively move the training programs for its employees rather than expanding its business for example by buying land for expansion of land and build office buildings and factories. Most of the mandatory disclosure required by the accounting profession in relation to physical capital. The recognition of intellectual capital as a pivotal factors for the company, making mandatory disclosure related to physical capital becomes less relevant for the user. This has led to gaps in information related to investment decision making. Therefore, standard setters should develop guidelines for the disclosure of intellectual capital in order to protect the interests of users (Suhardjanto and Wardhani, 2010).